Doing a Literature Review: Releasing the Social Science Research Imagination - Hart, Chris (London Sage Publications, 1998)
This book can provide an excellent framework for bolstering what is often an experiential process - doing a literature review. It is best seen alongside the supervisor, as a guide, through the multidimensional sea of academic literature' - British Educational Research Journal`I have been waiting for this book for five years. It sets out a number of important dimensions involved in the process of literature review and by clear signposting, diagrams, and examples will help the student to carry out her or his review more systematically. Learning how to carry out a literature review has always entailed the experiential. While this is a the best way of learning, it is only so providing that learning actually tak